Some results and impacts of 55th EOQ Congress in Budapest - Molnár, Pál; Marosi, Tibor; Gál, József; Véha, Antal (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The 55th EOQ A nnual C ongress w as organized by th e HNC for EOQ in Budapest between 20th-23rd June 2011. T his Congress was simultaneously also a World Quality Congress taking place triennially alternately in the United States, Europe and Japan. Considering that in this period Hungary had the Presidency of the EU Council, importance of this year’s World Quality Congress was underlined by the fact that it was also registered in the official EU calendar. Other important prestige increasing factors were the meeting of the representatives of the World Alliance for Quality (WAQ ), and the General Assembly of the International Academy of Quality (IAQ ) after the Congress. The most important presentations of the Congress are reviewed. In additions som econclusions and recommendations are summarised.